Successful Treatment of a Patient with Giant Cell Vasculitis (Horton Arteritis) with Tocilizumab a Humanized Anti-Interleukin-6 Receptor Antibody - Alfredomaria Lurati; Luca Bertani; Katia Angela Re; Mariagrazia Marrazza; Daniela Bompane; Magda Scarpellini (Case Reports in Rheumatology, 2012)
Giant cell arteritis (GCA) is the most common form of systemic vasculitis in adults, affecting preferentially medium-large size arteries. Here we report a case of a female with a diagnosis of GCA based on temporal artery biopsy, successfully treated with tocilizumab, a humanized anti-interleukin-6 receptor antibody.